Short screening scales to monitor population prevalances and trends in non-specific psychological distress - Kessler, Ronald; Andrews, Gavin; Colpe, Lisa; Hiripi, E; Mroczek, Daniel; Normand, Sharon-Lise; Walters, Ellen; Zaslavsky, Alan (Psychological Medicine, 2002)
A 10-question screening scale of psychological distress and a six-question short-form scale embedded within the 10-question scale were developed for the redesigned US National Health Interview Survey (NHIS). Initial pilot questions were administered in a US national mail survey (N = 1401). A reduced set of questions was subsequently administered in a US national telephone survey (N = 1574). The 10-question and six-question scales, which we refer to as the K10 and K6, were constructed from the reduced set of questions based on Item Response Theory models. The scales were subsequently validated in a two-stage clinical reappraisal survey (N = 1000 telephone screening interviews in the first stage followed by N = 153 face-to-face clinical interviews in the second stage that oversampled first-stage respondents who screened positive for emotional problems) in a local convenience sample. The second-stage sample was administered the screening scales along with the Structured Clinical Interview for DSM-IV (SCID). The K6 was subsequently included in the 1997 (N = 36116) and 1998 (N = 32440) US National Health Interview Survey, while the K10 was included in the 1997 (N = 10641) Australian National Survey of Mental Health and Well-Being. Both the K10 and K6 have good precision in the 90th-99th percentile range of the population distribution (standard errors of standardized scores in the range 0.20-0.25) as well as consistent psychometric properties across major sociodemographic subsamples. The scales strongly discriminate between community cases and non-cases of DSM-IV/SCID disorders, with areas under the Receiver Operating Characteristic (ROC) curve of 0.87-0.88 for disorders having Global Assessment of Functioning (GAF) scores of 0-70 and 0.95-0.96 for disorders having GAF scores of 0-50. The brevity, strong psychometric properties, and ability to discriminate DSM-IV cases from non-cases make the K10 and K6 attractive for use in general-purpose health surveys. The scales are already being used in annual government health surveys in the US and Canada as well as in the WHO World Mental Health Surveys. Routine inclusion of either the K10 or K6 in clinical studies would create an important, and heretofore missing, crosswalk between community and clinical epidemiology.

Exploring the backgrounds and shaping of beginning student teachers in Ghana: toward greater contextualisation of teacher education - Akyeampong, Kwame; Stephens, David (International Journal of Educational Development, 2002)
Teacher education programmes are often quite similar in their framework and content but often lack sufficient reflection on the personal background and the socio-political forces that shape teachers’ roles and identity within the systems in which they operate. This paper explores this issue by using Ghana as a case study and discusses implications for its teacher education programmes and policies. Key characteristics of beginning student teachers found were: weak qualifying grades in two fundamental school subjects, mathematics and English, a waiting period of 2–5 years prior to entering teachers’ college, and apparently sharp differentials in trainees’ socio-economic background as compared to typical Ghanaian communities. They come to training with rich and varied images of teachers, teaching and the profession, but, in addition, many beginning trainees also express little desire to teach at primary school level, mainly for reasons of status and insufficient fringe benefits. These factors, we argue, should be taken into more account in the design of college programmes and the development of teacher education policies. The paper concludes with a call to teacher education systems, especially in Africa, to look more closely at, and learn from, who comes for training, what they bring with them, and how they perceive themselves in relation to teaching, training and future aspirations.
Keywords: Beginning student teachers; Ghana; Teacher education; Teacher identity; Teacher images